2011
DOI: 10.1161/circgenetics.110.958926
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Endothelial Transcriptome In Vivo

Abstract: Background Endothelial function is central to the localization of atherosclerosis. The in vivo endothelial phenotypic footprints of arterial bed identity and site-specific athero-susceptibility are addressed. Methods and Results 98 endothelial cell samples from 13 discrete coronary and non-coronary arterial regions of varying susceptibilities to atherosclerosis were isolated from 76 normal swine. Transcript profiles were analyzed to determine the steady state in vivo endothelial phenotypes. An unsupervised s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 56 publications
(62 reference statements)
0
35
0
Order By: Relevance
“…We found that the LAD, a classically "atheroprone" coronary artery in adulthood (2,18), is more susceptible to transcriptional alterations as a result of juvenile obesity, compared with the more "atheroresistant" descending thoracic aorta (17). Notably, we identified a number of genes in the LAD (e.g., ACP5, LYZ, CXCL14, APOE, PLA2G7, LGALS3, SPP1, ITGB2, CYBB, P2RY12) that are implicated in atherosclerosis based on published literature (1, 10, 22-24, 27, 32, 33, 45, 48, 51, 56, 64, 74, 77, 84) and whose expression was markedly upregulated with juvenile obesity.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We found that the LAD, a classically "atheroprone" coronary artery in adulthood (2,18), is more susceptible to transcriptional alterations as a result of juvenile obesity, compared with the more "atheroresistant" descending thoracic aorta (17). Notably, we identified a number of genes in the LAD (e.g., ACP5, LYZ, CXCL14, APOE, PLA2G7, LGALS3, SPP1, ITGB2, CYBB, P2RY12) that are implicated in atherosclerosis based on published literature (1, 10, 22-24, 27, 32, 33, 45, 48, 51, 56, 64, 74, 77, 84) and whose expression was markedly upregulated with juvenile obesity.…”
Section: Discussionmentioning
confidence: 83%
“…Because it is well established that coronary arteries, particularly the LAD, are highly susceptible to atherosclerosis (2,18) relative to other vascular beds such as the descending thoracic aorta (17), the changes in vascular gene expression produced by juvenile obesity that are exclusive to the LAD are of particular interest. In this regard, a number of genes found to be markedly upregulated in the LAD of obese pigs are implicated in the progression of atherosclerosis, including ACP5, LYZ, CXCL14, APOE, PLA2G7, LGALS3, SPP1, ITGB2, CYBB, and P2RY12 (Table 3) (1, 10, 22-24, 27, 32, 33, 45, 48, 51, 56, 64, 74, 77, 84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, biological networks and modules have been described in atherosclerosis, like the transcriptomic modules derived from transcriptomic data of the Karolinska University Hospital, and constructed a gene association and correlation network of atherosclerosis (29). The coronary artery endothelial transcriptome was addressed in an experimental study and the transcript profiles were analyzed to identify the in vivo endothelial phenotypes (30). In a gene connectivity network analysis, specific coronary endothelial phenotypes expressed in gene modules were related to increased endoplasmic reticulum and oxidative stress in coronary arteries prone to atherosclerosis (30).…”
Section: Biological Networkmentioning
confidence: 99%
“…The coronary artery endothelial transcriptome was addressed in an experimental study and the transcript profiles were analyzed to identify the in vivo endothelial phenotypes (30). In a gene connectivity network analysis, specific coronary endothelial phenotypes expressed in gene modules were related to increased endoplasmic reticulum and oxidative stress in coronary arteries prone to atherosclerosis (30).…”
Section: Biological Networkmentioning
confidence: 99%